Efficient and Highly Enantioselective Aerobic Oxidation–Michael–Carbocyclization Cascade Transformations by Integrated Pd(0)-CPG Nanoparticle/Chiral Amine Relay Catalysis - Deiana, Luca; Ghisu, Lorenza; Córdova, Oscar; Afewerki, Samson; Zhang, Renyun; Córdova, Armando (Synthesis, 2014)
A series of highly diastereo- and enantioselective aerobic oxidation–Michael–carbocyclization cascade transformations by integrated heterogeneous Pd(0)-CPG nanoparticle/chiral amine relay catalysis are disclosed. The heterogeneous Pd(0)-CPG nanoparticle catalysts were efficient for both the sequential aerobic oxidation and dynamic kinetic asymmetric Michael–carbocyclization transformations, resulting in 1) oxidation of a variety of allylic alcohols to enals and 2) formation of cyclopentenes containing an all-carbon quaternary stereocenter in good to high yields with up to 20:1 dr and 99.5:0.5 er.
Keywords: asymmetric cocatalysis; aerobic oxidations; relay catalysis; integrated heterogeneous catalysis; integrated homogeneous catalysis; quaternary stereocenters